Contextual variables and training load throughout a competitive period in a top-level male soccer team - Rago, V.; Rebelo, A.; Krustrup, P.; Mohr, M. (The Journal of Strength and Conditioning Research, 2021)
The aim of the present study was to investigate and quantify the weekly training load (TL) according to different match-related contextual factors in a professional male soccer team (n = 23). Training load was quantified using a 10-Hz global positioning system with integrated 100-Hz accelerometer and heart rate recordings over a 3-month competitive period. Total distance (TD) covered and high-speed running (HSR, >16 km·h-1) during training were higher in the week after playing against a bottom-level or top-level opponent compared to a medium-level opponent (p < 0.05; effect size [ES] = 0.30-1.04). TD was also higher when preparing for a match against a bottom-level opponent (p < 0.05; ES = 0.39-0.76). In addition, the percentage of HSR was higher after playing a bottom-level compared to a medium-level opponent (p < 0.001; ES = 0.49 [0.27; 0.71]). TD covered was higher in the week following a draw or a win, and higher before a loss compared to a draw (p < 0.05, ES = 0.32-0.81). Both absolute HSR and HSR expressed as percentage of TD were higher before losing and winning a match compared to a draw (p < 0.05; ES = 0.72-0.98). Weekly TL seems to be slightly affected by match-related contextual variables, with special emphasis on the opponent standard and match outcome. Higher training volume was observed before and after playing against a top-level opponent, and after losing a match, whereas the volume of high-intensity training seems to be higher when preparing for a game against a top-level opponent. Future experimental research should clarify the interaction between match-related contextual variables (e.g., cause) and weekly TL (e.g., effect).